2010
DOI: 10.1007/s00384-010-0907-8
|View full text |Cite|
|
Sign up to set email alerts
|

Phenotypic diversity in patients with multiple serrated polyps: a genetics clinic study

Abstract: ObjectiveHyperplastic polyposis is a colonic polyposis condition of unknown aetiology. The purpose of this study was to examine the spectrum of phenotypic variation in patients with multiple serrated polyps as a basis for gene discovery.MethodsOne hundred and twenty-six patients with multiple (≥5) serrated polyps were recruited to the study. Polyp counts were extracted from histology and colonoscopy reports. Ethnicity was self-reported. Family history of cancer data were derived from pedigrees. Ascertainment s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
49
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 36 publications
2
49
1
1
Order By: Relevance
“…SSAs are considered the main precursor of CRC in HPS, its scarcity in our sample may explain the low number of CRC cases, in opposition to the works of Buchanan [24] or Lage et al [17] in which 40% of patients had CRC. Interestingly, in our single case of adenocarcinoma, the tumor was grafted in TA.…”
Section: Discussioncontrasting
confidence: 63%
“…SSAs are considered the main precursor of CRC in HPS, its scarcity in our sample may explain the low number of CRC cases, in opposition to the works of Buchanan [24] or Lage et al [17] in which 40% of patients had CRC. Interestingly, in our single case of adenocarcinoma, the tumor was grafted in TA.…”
Section: Discussioncontrasting
confidence: 63%
“…3,9,10,15 In the three largest series published to date, 11 25% to 38% of serrated polyposis patients presented with at least one CRC, and multiple CRCs were common. 16 This relatively low rate of CRC in our study could be explained by the fact that partial or subtotal colectomy was performed in 51.7% of our patients. In our experience, despite the fact that a majority of our patients had at least partial colectomy, there is a significant place for endoscopic treatment in patients with sessile serrated polyposis.…”
Section: Discussionmentioning
confidence: 71%
“…18 On the contrary, Huang et al found no association between smoking and advanced serrated polyps. 19 Current smoking was associated with a significantly higher polyp number in patients with serrated polyposis, 16 and the prevalence of current smokers was higher among serrated polyposis patients than in the general population. 11,20 Our study confirms a high rate of tobacco users in type 1 serrated polyposis patients with 82.8% of smokers (a rate of 65.6% is usual in the literature): i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It became known that colon cancer can be the product of a mutation of several genes, each having sensitivity to environmental factors, such as smoking, physical inactivity, overweight and obesity, consumption of red meat and excessive alcohol consumption [6]. We know that with an increase in the life expectancy the risk of developing of CRC also increases, which is associated with an increased risk of CIMP-high BRAF-mutated CRC [7]. Recent data suggest that the probability of CRC is higher in family members of patients with BRAF-mutated CRC, than in patients without a family history [8].…”
mentioning
confidence: 99%